2012
DOI: 10.1371/journal.pone.0041147
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Inhibits the Development of Atherosclerosis with Suppressing CX3CR1 and CX3CL1 Expression

Abstract: Hydrogen sulfide, as a novel gaseous mediator, has been suggested to play a key role in atherogenesis. However, the precise mechanisms by which H2S affects atherosclerosis remain unclear. Therefore, the present study aimed to investigate the potential role of H2S in atherosclerosis and the underlying mechanism with respect to chemokines (CCL2, CCL5 and CX3CL1) and chemokine receptors (CCR2, CCR5, and CX3CR1) in macrophages. Mouse macrophage cell line RAW 264.7 or mouse peritoneal macrophages were pre-incubated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 38 publications
3
56
0
2
Order By: Relevance
“…In this latter work, the rate of development of atherosclerosis in these animals could be reduced by replacement therapy with NaHS. The current consensus is therefore that lack of H 2 S contributes to accelerated progression of atherosclerosis (Szab o et al 2011;Xu et al 2014a;Zhang et al 2012). …”
Section: 2mentioning
confidence: 99%
“…In this latter work, the rate of development of atherosclerosis in these animals could be reduced by replacement therapy with NaHS. The current consensus is therefore that lack of H 2 S contributes to accelerated progression of atherosclerosis (Szab o et al 2011;Xu et al 2014a;Zhang et al 2012). …”
Section: 2mentioning
confidence: 99%
“…NaHS (100 µmol/L for 12 hrs) inhibited ICAM-1 expression in TNF-alpha-induced HUVECs via the NF-kB pathway [159]. Moreover, NaHS administration concentration-dependently (50-200 µM) reduced CX3CR1 and CX3CL1 expression in mouse peritoneal macrophages as well as CX3CR1-mediated chemotaxis [160]. In fat-fed apoE-KO mice, NaHS (1 mg/kg, i.p., daily) attenuated, and PPG (10 mg/kg, i.p., daily) exacerbated, the extent of atherosclerotic plaques [160].…”
Section: The Roles Of H 2 S and No In Atherosclerosismentioning
confidence: 99%
“…Moreover, NaHS administration concentration-dependently (50-200 µM) reduced CX3CR1 and CX3CL1 expression in mouse peritoneal macrophages as well as CX3CR1-mediated chemotaxis [160]. In fat-fed apoE-KO mice, NaHS (1 mg/kg, i.p., daily) attenuated, and PPG (10 mg/kg, i.p., daily) exacerbated, the extent of atherosclerotic plaques [160]. H 2 S (50 µM) attenuated H 2 O 2 and oxidized LDL (oxLDL)-mediated endothelial cytotoxicity in HUVECs [161].…”
Section: The Roles Of H 2 S and No In Atherosclerosismentioning
confidence: 99%
“…Besides, NaHS inhibited ICAM-1 expression induced by tumor necrosis factor (TNF)-α stimulation via hampering IκB degradation in HUVECs [113]. Furthermore, Wang et al [114] suggested that H 2 S inhibited progression of atherosclerosis in ApoE KO mice with high-fat diet via downregulating CX3CR1 and CX3CL1 expression on macrophages in the lesion plaque in vivo . In addition, exogenous NaHS achieved its beneficial effects on diabetes accelerated atherosclerosis by inducing KEAP1 sulfhydration and NRF2 activation [51].…”
Section: Evidence Related To Atherosclerosis Prevention and Treatmentmentioning
confidence: 99%